An antistatic agent for crude oil FDY oiling agent and preparation method thereof
By introducing quaternary ammonium salt-based polyionic liquids and nanosols into the antistatic agents, the problems of poor washing resistance and uneven antistatic effects of existing antistatic agents are solved, and the efficient antistatic and water resistance of fabrics are achieved.
Patent Information
- Application Number
- CN202411529101.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing antistatic agents have poor washing resistance and uneven distribution of antistatic effects, making it difficult to effectively prevent the generation and propagation of static electricity during spinning.
By reacting 3-vinylbenzyl chloride with the esterified product and antioxidant under an inert atmosphere, a quaternary ammonium salt-based polyionic liquid antistatic agent is generated, and alumina sol and silica sol are added to form a Si/Al composite sol to improve the antistatic properties and water resistance of the fabric.
It significantly improves the anti-static properties and water resistance of the fabric, ensures the uniformity and durability of the anti-static effect, and effectively solves the electrostatic problems during spinning.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antistatic agents, and in particular relates to an antistatic agent for crude oil FDY oiling agent and a preparation method thereof. Background Art
[0002] Chemical fiber is the most commonly used and widely used textile raw material. It has excellent properties, but due to its inherent low regain and large inherent surface resistivity, a large amount of static electricity is generated during the spinning process due to the continuous friction between fibers. If the static electricity cannot be well dissipated, it will cause abnormalities in the spinning process, including the silk strips being easy to slip and scatter, causing problems such as hairy silk and waste silk, thus affecting the normal production. The elimination of static electricity first prevents the accumulation of charges and reduces the generation of static electricity at the source. Previous studies have shown that the charge increases with the increase in the number of contacts. Therefore, reducing the number of frictions can effectively reduce the generation of charges. However, it is actually impossible to produce no friction during the fiber production process. Therefore, oils must be used. On the one hand, the lubricating effect of the oil can greatly reduce the friction. On the other hand, the antistatic agent contained in the oil can make the surface charge of the fiber flow rapidly and promote discharge.
[0003] A Chinese patent with publication number CN117845379B discloses a process for preparing a highly efficient antistatic agent for chemical fiber oils, comprising the steps of adding sulfur-doped Mxene to anhydrous ethanol A for ultrasonic treatment to obtain a sulfur-doped Mxene ethanol dispersion; dropping a nitrogen-containing compound ethanol solution into the sulfur-doped Mxene ethanol dispersion to obtain a mixed solution, adding the mixed solution into a hydrothermal kettle for heat treatment to obtain a precipitate, washing the precipitate, and vacuum drying to obtain nitrogen-sulfur doped Mxene; adding nitrogen-sulfur doped Mxene and an antistatic agent to anhydrous ethanol C and stirring; then applying dual-frequency ultrasonic treatment, separating, and vacuum drying to obtain a highly efficient antistatic agent for chemical fiber oils; and preparing a highly efficient antistatic agent for chemical fiber oils with excellent antistatic properties by combining nitrogen-sulfur doped Mxene with an antistatic agent, and solving the problem of poor compatibility of existing antistatic agents with other components in chemical fiber oils. A Chinese patent with publication number CN108547149B discloses a method for preparing an antistatic agent for spinning oil, wherein an alkyl polyoxyethylene oxypropylene alcohol and phosphorus pentoxide powder are mixed, subjected to a temperature-raising reaction, and then a graphene oxide solution is added to react to obtain an antistatic agent for spinning oil. Due to the introduction of graphene and polyether segments, the compatibility and permeability of the spinning oil with the fiber matrix can be increased, and the smoothness and bundling of the fiber can be improved. Graphene with good electrical conductivity is introduced into the molecular structure through a chemical reaction, thereby further improving the antistatic performance of the product.
[0004] However, most of the antistatic agents in the prior art have a straight-chain structure, which has the disadvantages of poor washing resistance and uneven distribution of antistatic effect. Therefore, the preparation of an antistatic agent with good washing resistance and antistatic performance has become a research focus. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides an antistatic agent for crude oil FDY oil agent and a preparation method thereof, wherein an ionic liquid monomer is synthesized by using an esterification product generated by the reaction of 4-vinylbenzyl chloride and triethanolamine with a diol, and a quaternary ammonium salt polyionic liquid antistatic agent is further synthesized, and an alumina sol and a silica sol are also added, thereby effectively improving the antistatic property and water resistance of the fabric.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing an antistatic agent for FDY oiling agent for crude oil, comprising the following steps:
[0008] S100, mixing triethanolamine and dibasic acid, adding a catalyst, and heating to react to obtain an esterification product;
[0009] S200, under an inert atmosphere, mixing 4-vinylbenzyl chloride, an esterification product and an antioxidant, and after the temperature reaction is completed, washing, filtering and drying to obtain a powdery solid;
[0010] S300, under an inert atmosphere, mixing a powdered solid and isopropanol, heating the mixture for 1-2 hours, adding a polymerization initiator, and continuing the reaction for 22-28 hours, raising the temperature, recovering the isopropanol, adding a KPF6 salt solution, stirring at room temperature for 50-60 hours, washing, filtering, and drying to obtain a white solid;
[0011] S400, preparing an alumina sol using aluminum isopropoxide and isopropanol, preparing a silica sol using 3-aminopropyltriethoxysilane, and mixing the alumina sol and the silica sol to obtain a Si / Al composite sol;
[0012] S500, mixing the obtained white solid with Si / Al composite sol to obtain the antistatic agent.
[0013] Furthermore, in step S100, the structural formula of the dibasic acid is COOH-(CH2) n -COOH, wherein n is a positive integer not less than 4 and not more than 10.
[0014] Further, step S100 specifically includes: after mixing triethanolamine and dibasic acid, raising the temperature to 90-105° C., stirring until all solids are dissolved, then adding a catalyst thereto, raising the temperature to 120-135° C., stirring for 4-6 hours, and obtaining an esterification product.
[0015] Furthermore, the catalyst is p-toluenesulfonic acid; the dibasic acid is adipic acid; and the mass ratio of triethanolamine, adipic acid and catalyst is 1:3-4:0.1-0.13.
[0016] Most of the antistatic agents currently available on the market have a straight-chain structure, which has poor bonding with fabrics, and has problems such as poor water resistance and poor antistatic effect. In order to make the antistatic performance continuously effective, the antistatic agent needs to have a certain affinity with the fiber surface, and at the same time, the antistatic agent molecules cannot be attached too tightly, otherwise it will interfere with the mobility of the molecules and affect the antistatic effect; therefore, in step S100, triethanolamine and diol are used to undergo an esterification reaction to generate a network esterification product; compared with the branched structure, the network structure can increase the contact area with the fiber, and at the same time, the esterification product generated by the reaction of triethanolamine and diol has ester groups, which can increase the compatibility with the fiber and effectively increase the water resistance.
[0017] Furthermore, step S200 is specifically as follows: under an inert atmosphere, 4-vinylbenzyl chloride, the esterification product and the antioxidant are mixed, the temperature is increased to 75-85°C, and flocculent solids appear after stirring for 5-10 minutes. After the reaction is continued for 25-30 hours, the plate is tapped several times to monitor the reaction. When the raw material is <30% and the rate of change is <1% after continuous sampling for 1 hour, the reaction is terminated. When the system is cooled to 40°C, it is washed, filtered and dried to obtain a powdered solid.
[0018] Furthermore, the antioxidant is 2,6-di-tert-butyl-4-methylphenol; the inert atmosphere is nitrogen; the mass ratio of 4-vinylbenzyl chloride, esterification product and antioxidant is 1:1.4-2:0.1-0.13; and the drying conditions are: drying in a vacuum drying oven at 40-50°C to constant weight.
[0019] Further, step S300 specifically includes: under an inert atmosphere, mixing the powdered solid and isopropanol, raising the temperature to 75-90°C to react for 1-2 hours, adding a polymerization initiator to continue the reaction for 22-28 hours, and then raising the temperature to 95-105°C, condensing and recovering the isopropanol, and when no isopropanol drips out, adding KPF6 salt solution thereto, stirring at room temperature for 50-60 hours, washing, filtering, and drying to obtain a white solid.
[0020] Furthermore, the polymerization initiator is azobisisobutyronitrile; the inert atmosphere is nitrogen; the mass ratio of the powdered solid, isopropanol and the polymerization initiator is 1:2-3:0.1-0.13; the mass ratio of the powdered solid and KPF6 is 4:3-4, and the drying conditions are: drying in a vacuum drying oven at 80-100°C to constant weight.
[0021] Furthermore, the preparation method of KPF6 salt solution is: add KPF6 into deionized water at 65°C and stir until dissolved; wherein the amount of KPF6 used is 0.25-0.35g / mL.
[0022] Ionic liquids have certain lubricity and wear resistance, can reduce the static charge generated by friction of polymer materials, and have antistatic properties and good thermal stability, so they can be used as the main component of antistatic agents; ionic liquids are mainly composed of organic cations and anions, and their unique structure can introduce different functions and properties respectively, and can be designed according to the physical and chemical properties of the desired target; polyelectrolytes composed of the polymer skeleton and ionic liquid in the ionic liquid monomer repeating unit are polyionic liquids, which, compared with ionic liquids, not only have the advantages of ionic liquids, but also overcome the disadvantages of ionic liquids such as high viscosity. Since some polyionic liquids have certain water absorption, they can absorb water on the surface of the substrate to form a thin layer of water, thereby forming a uniform conductive network structure, which is conducive to the elimination of static electricity; therefore, in steps S200 and S300, ionic liquid monomers are synthesized using 4-vinylbenzyl chloride and the esterification product prepared in step S100, and quaternary ammonium salt polyionic liquid antistatic agents are further synthesized.
[0023] Furthermore, step S400 specifically includes:
[0024] S410, preparation of alumina sol: add deionized water to a reactor, raise the temperature to 85°C, add aluminum isopropoxide solution in portions after constant temperature, reflux and stir for 2-3 hours after all the addition is completed to form a white precipitate, then raise the temperature to 95°C, evaporate under stirring until the isopropanol is completely volatilized, add hydrochloric acid to redisperse the precipitate, and age for 4 hours to obtain alumina sol;
[0025] S420, preparation of silica sol: adding 3-aminopropyltriethoxysilane and deionized water into a reactor, stirring at room temperature until a clear and transparent solution is obtained to obtain silica sol;
[0026] S430, mixing the aluminum oxide sol and the silicon oxide sol in a mass ratio of 1-3:1 to obtain a Si / Al composite sol.
[0027] Further, in step S410, the concentration of hydrochloric acid is 2 mol / L, and the mass ratio of aluminum isopropoxide solution, deionized water and hydrochloric acid is 1:1.5-3:0.2-0.3;
[0028] Further, in step S410, the preparation method of the aluminum isopropoxide solution is: mixing aluminum isopropoxide and isopropanol in a mass ratio of 1:1.5-2.5;
[0029] Further, in step S420, the mass ratio of 3-aminopropyltriethoxysilane to deionized water is 5-8:25-35.
[0030] Since nanomaterials have the characteristics of small size effect, surface effect and quantum size that conventional coarse crystals do not have, nanomaterials are easy to disperse, have good compatibility and easy to combine. After being coated on the surface of the fabric, they are easy to penetrate into the surface of the fiber under high temperature due to their small size effect, thereby being enriched on the surface and playing an anti-static role; silica sol can form a complex three-dimensional network structure on the surface of the fabric, which can effectively improve the anti-static performance of the fabric without affecting the strength and gloss of the fabric; alumina sol is used in the finishing process of polyester fabric to effectively improve its anti-static property; therefore, in step S400, alumina sol with good stability and uniformity is prepared by hydrolyzing aluminum isopropanol and dissolving with hydrochloric acid; and silica sol is prepared by in-situ generation by hydrolysis of 3-aminopropyltriethoxysilane; compared with directly adding nano alumina and nano silica particles, it is not easy to agglomerate and has good dispersion performance.
[0031] Further, in step S500, the mass ratio of the white solid to the Si / Al composite sol is 2-5:15.
[0032] The present invention also provides an antistatic agent for FDY oiling agent for crude oil, and the antistatic agent is obtained by using the preparation method of any one of the above technical solutions.
[0033] The present invention has the following beneficial effects:
[0034] The invention uses esterification products generated by the reaction of 4-vinylbenzyl chloride and triethanolamine with diol to synthesize ionic liquid monomers, further synthesizes quaternary ammonium salt polyionic liquid antistatic agents, and further adds aluminum oxide sol and silicon oxide sol to effectively improve the antistatic performance of fabrics; the network structure synthesized by triethanolamine and diols has a larger contact area with the fabric than a straight chain structure, and can effectively enhance the bonding performance with the fabric; the ester group contained can increase the compatibility with the fiber and effectively increase the water resistance; the quaternary ammonium salt polyionic liquid has a certain water absorption, and can absorb water on the surface of the substrate to form a thin layer of water, thereby forming a uniform conductive network structure, which can effectively eliminate static electricity; and the addition of aluminum oxide sol and silicon oxide sol can penetrate into the surface of the fiber, enrich in the surface layer, and further improve the antistatic performance of the fabric. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0036] Triethanolamine (AR), adipic acid (AR), p-toluenesulfonic acid, aluminum isopropoxide (purity 98%), and 3-aminopropyltriethoxysilane (98%) used in the present invention were all purchased from Sinopharm Chemical Reagent Co., Ltd., 4-vinylbenzyl chloride (purity 98%), 2,6-di-tert-butyl-4-methylphenol (analytical grade), isopropanol (analytical grade), and potassium hexafluorophosphate (purity 99%) were all purchased from MacLean Chemical Reagent Network, and all reagents were commercially available.
[0037] Example 1
[0038] A method for preparing an antistatic agent for FDY oiling agent for crude oil, comprising the following steps:
[0039] S100, after mixing triethanolamine and adipic acid, raising the temperature to 95° C., stirring until all the solids are dissolved, then adding p-toluenesulfonic acid thereto, raising the temperature to 125° C., stirring for 5 hours, to obtain an esterification product; wherein the mass ratio of triethanolamine, adipic acid and catalyst p-toluenesulfonic acid is 1:3.2:0.12;
[0040] S200, under a nitrogen atmosphere, 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol were mixed and the temperature was raised to 80°C. After stirring for 8 minutes, flocculent solids appeared. After continuing the reaction for 28 hours, the plate was tapped several times to monitor the reaction. When the raw material was <30% and the rate of change was <1% after continuous sampling for 1 hour, the reaction was terminated. When the system was cooled to 40°C, it was washed, filtered and dried to obtain a powdered solid; wherein the mass ratio of 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol was 1:1.6:0.12; the drying conditions were: dried in a vacuum drying oven at 45°C to constant weight;
[0041] S300, under a nitrogen atmosphere, the powdered solid and isopropanol are mixed, the temperature is raised to 80°C for reaction for 1.5h, azobisisobutyronitrile is added, the reaction is continued for 25h, the temperature is raised to 100°C, isopropanol is condensed and recovered, and when no isopropanol drips out, KPF6 salt solution is added thereto, stirred at room temperature for 55h, washed, filtered and dried to obtain a white solid; wherein the mass ratio of the powdered solid, isopropanol and azobisisobutyronitrile is 1:2.5:0.12; the mass ratio of the powdered solid and KPF6 is 4:3, and the drying conditions are: dried in a vacuum drying oven at 90°C to constant weight; wherein the preparation method of the KPF6 salt solution is: adding KPF6 to deionized water at 65°C and stirring until dissolved; wherein the amount of KPF6 is 0.3g / mL;
[0042] S400, using aluminum isopropoxide and isopropanol to prepare an alumina sol, using 3-aminopropyltriethoxysilane to prepare a silica sol, and mixing the alumina sol and the silica sol to obtain a Si / Al composite sol; specifically:
[0043] S410, preparation of alumina sol: adding deionized water to a reactor, raising the temperature to 85° C., adding aluminum isopropoxide solution in portions after constant temperature, and after all the addition, reflux and stir for 2 hours to form a white precipitate, then raising the temperature to 95° C., evaporating under stirring until isopropanol is completely volatilized, adding hydrochloric acid to redisperse the precipitate, and aging for 4 hours to obtain alumina sol; wherein the concentration of hydrochloric acid is 2 mol / L, and the mass ratio of aluminum isopropoxide solution, deionized water and hydrochloric acid is 1:1.8:0.25; the preparation method of aluminum isopropoxide solution is: mixing aluminum isopropoxide and isopropanol in a mass ratio of 1:2;
[0044] S420, preparation of silica sol: adding 3-aminopropyltriethoxysilane and deionized water into a reactor, stirring at room temperature until a clear transparent solution is obtained to obtain silica sol; wherein the mass ratio of 3-aminopropyltriethoxysilane to deionized water is 7:32;
[0045] S430, mixing the aluminum oxide sol and the silicon oxide sol in a mass ratio of 2:1 to obtain a Si / Al composite sol;
[0046] S500, mixing the obtained white solid with Si / Al composite sol to obtain an antistatic agent; wherein the mass ratio of the white solid to the Si / Al composite sol is 4:15.
[0047] Example 2
[0048] This embodiment is different from Embodiment 1 in the following aspects:
[0049] In step S100, after triethanolamine and adipic acid are mixed, the temperature is raised to 90° C., p-toluenesulfonic acid is added, the temperature is raised to 120° C., and the mixture is stirred for 4 hours to obtain an esterification product; wherein the mass ratio of triethanolamine, adipic acid and catalyst is 1:3:0.1;
[0050] In step S200, 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol are mixed and the temperature is increased to 75°C. After stirring for 5 minutes, a flocculent solid appears. After continuing the reaction for 25 hours, the plate is tapped several times to monitor the reaction. When the raw material is <30% and the change rate is <1% measured by continuous sampling for 1 hour, the reaction is terminated. When the system is cooled to 40°C, it is washed, filtered and dried to obtain a powdered solid; wherein the mass ratio of 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol is 1:1.4:0.1; the drying conditions are: drying in a vacuum drying oven at 40°C to constant weight;
[0051] In step S300, the powdered solid and isopropanol are mixed, the temperature is raised to 75°C for reaction for 1 hour, azobisisobutyronitrile is added, the reaction is continued for 22 hours, the temperature is raised to 95°C, the isopropanol is condensed and recovered, and when no isopropanol drips out, KPF6 salt solution is added thereto, stirred at room temperature for 50 hours, washed, filtered, and dried to obtain a white solid. The mass ratio of the powdered solid, isopropanol, and azobisisobutyronitrile is 1:2:0.1; the mass ratio of the powdered solid and KPF6 is 4:3, and the drying conditions are: dried in a vacuum drying oven at 80°C to constant weight; the preparation method of the KPF6 salt solution is: adding KPF6 to deionized water at 65°C and stirring until dissolved; the amount of KPF6 used is 0.25g / mL;
[0052] In step S410, the mass ratio of aluminum isopropoxide solution, deionized water and hydrochloric acid is 1:1.5:0.2; the preparation method of the aluminum isopropoxide solution is: mixing aluminum isopropoxide and isopropanol in a mass ratio of 1:1.5;
[0053] In step S420, the mass ratio of 3-aminopropyltriethoxysilane to deionized water is 5:25;
[0054] In step S430, the aluminum oxide sol and the silicon oxide sol are mixed uniformly in a mass ratio of 1:1;
[0055] In step S500 , the mass ratio of the white solid to the Si / Al composite sol is 2:15.
[0056] The rest is as per Example 1.
[0057] Example 3
[0058] This embodiment is different from Embodiment 1 in the following aspects:
[0059] In step S100, after triethanolamine and adipic acid are mixed, the temperature is raised to 105° C., p-toluenesulfonic acid is added, the temperature is raised to 135° C., and the mixture is stirred for 4 hours to obtain an esterification product; wherein the mass ratio of triethanolamine, adipic acid and catalyst is 1:4:0.13;
[0060] In step S200, 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol are mixed and the temperature is increased to 85°C. After stirring for 10 minutes, a flocculent solid appears. After continuing the reaction for 30 hours, the plate is tapped several times to monitor the reaction. When the raw material is <30% and the change rate is <1% after continuous sampling for 1 hour, the reaction is terminated. When the system is cooled to 40°C, it is washed, filtered and dried to obtain a powdered solid; wherein the mass ratio of 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol is 1:2:0.13; the drying conditions are: drying in a vacuum drying oven at 50°C to constant weight;
[0061] In step S300, the powdered solid and isopropanol are mixed, the temperature is raised to 90°C for reaction for 2 hours, azobisisobutyronitrile is added, the reaction is continued for 28 hours, the temperature is raised to 105°C, the isopropanol is condensed and recovered, and when no isopropanol drips out, KPF6 salt solution is added thereto, stirred at room temperature for 60 hours, washed, filtered, and dried to obtain a white solid. The mass ratio of the powdered solid, isopropanol, and azobisisobutyronitrile is 1:3:0.13; the mass ratio of the powdered solid and KPF6 is 1:1, and the drying conditions are: dried in a vacuum drying oven at 100°C to constant weight; the preparation method of the KPF6 salt solution is: adding KPF6 to deionized water at 65°C and stirring until dissolved; the amount of KPF6 used is 0.35g / mL;
[0062] In step S410, the mass ratio of aluminum isopropoxide solution, deionized water and hydrochloric acid is 1:3:0.3; the preparation method of the aluminum isopropoxide solution is: mixing aluminum isopropoxide and isopropanol in a mass ratio of 1:2.5;
[0063] In step S420, the mass ratio of 3-aminopropyltriethoxysilane to deionized water is 8:35;
[0064] In step S430, the aluminum oxide sol and the silicon oxide sol are mixed uniformly in a mass ratio of 3:1;
[0065] In step S500 , the mass ratio of the white solid to the Si / Al composite sol is 5:15.
[0066] The rest is as per Example 1.
[0067] Comparative Example 1
[0068] Compared with Example 1, in the preparation process, only alumina sol was added, and silica sol was not added. The rest was referred to Example 1, specifically:
[0069] S400, adding deionized water to the reactor, raising the temperature to 85°C, adding aluminum isopropoxide solution in batches after constant temperature, and refluxing and stirring for 2 hours after all the addition to form a white precipitate, and then heating to 95°C, evaporating under stirring until isopropanol is completely volatilized, adding hydrochloric acid to redisperse the precipitate, and aging for 4 hours to obtain alumina sol; wherein the concentration of hydrochloric acid is 2moL / L, and the mass ratio of aluminum isopropoxide solution, deionized water and hydrochloric acid is 1:1.8:0.25; the preparation method of aluminum isopropoxide solution is: mixing aluminum isopropoxide and isopropanol in a mass ratio of 1:2;
[0070] S500, mixing the obtained white solid with alumina sol to obtain an antistatic agent; wherein the mass ratio of the white solid to the alumina sol is 4:15.
[0071] Steps S100 , S200 and S300 refer to those in Embodiment 1.
[0072] Comparative Example 2
[0073] Compared with Example 1, this comparative example does not add Si / Al composite sol during the preparation process, and the rest is referred to Example 1, specifically:
[0074] S100, after mixing triethanolamine and adipic acid, raising the temperature to 95° C., stirring until all the solids are dissolved, then adding p-toluenesulfonic acid thereto, raising the temperature to 125° C., stirring for 5 hours, to obtain an esterification product, wherein the mass ratio of triethanolamine, adipic acid and catalyst is 1:3.2:0.12;
[0075] S200, under a nitrogen atmosphere, 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol were mixed and the temperature was raised to 80°C. After stirring for 8 minutes, flocculent solids appeared. After continuing the reaction for 28 hours, the plate was tapped several times to monitor the reaction. When the raw material was <30% and the rate of change was <1% after continuous sampling for 1 hour, the reaction was terminated. When the system was cooled to 40°C, it was washed, filtered and dried to obtain a powdered solid; wherein the mass ratio of 4-vinylbenzyl chloride, esterification product and 2,6-di-tert-butyl-4-methylphenol was 1:1.6:0.12; the drying conditions were: dried in a vacuum drying oven at 45°C to constant weight;
[0076] S300. Under a nitrogen atmosphere, a powdered solid and isopropanol are mixed, the temperature is raised to 80°C for reaction for 1.5 hours, azobisisobutyronitrile is added, the reaction is continued for 25 hours, the temperature is raised to 100°C, isopropanol is condensed and recovered, and when no isopropanol drips out, KPF6 salt solution is added thereto, stirred at room temperature for 55 hours, washed, filtered and dried to obtain a white solid, which is an antistatic agent; wherein the mass ratio of the powdered solid, isopropanol and azobisisobutyronitrile is 1:2.5:0.12; the mass ratio of the powdered solid and KPF6 is 4:3, and the drying conditions are: dried in a vacuum drying oven at 90°C to constant weight; wherein the preparation method of the KPF6 salt solution is: adding KPF6 to deionized water at 65°C and stirring until dissolved; wherein the amount of KPF6 is 0.3 g / mL.
[0077] Comparative Example 3
[0078] Compared with Example 1, this comparative example uses triethylamine instead of the esterification product to prepare the antistatic agent, and the rest is referred to Example 1, specifically:
[0079] S100, under nitrogen atmosphere, 4-vinylbenzyl chloride, triethylamine and 2,6-di-tert-butyl-4-methylphenol were mixed and the temperature was raised to 80°C. After stirring for 8 minutes, flocculent solids appeared. After continuing the reaction for 28 hours, the plate was tapped several times to monitor the reaction. When the raw material was <30% and the rate of change was <1% after continuous sampling for 1 hour, the reaction was terminated. When the system was cooled to 40°C, it was washed, filtered and dried to obtain a powdered solid; wherein the mass ratio of 4-vinylbenzyl chloride, triethylamine and 2,6-di-tert-butyl-4-methylphenol was 1:1.6:0.12; the drying conditions were: dried in a vacuum drying oven at 45°C to constant weight;
[0080] S200, under a nitrogen atmosphere, the powdered solid and isopropanol were mixed, the temperature was raised to 80°C for reaction for 1.5h, azobisisobutyronitrile was added, the reaction was continued for 25h, the temperature was raised to 100°C, isopropanol was condensed and recovered, and when no isopropanol dripped out, KPF6 salt solution was added thereto, stirred at room temperature for 55h, washed, filtered and dried to obtain a white solid; wherein the mass ratio of the powdered solid, isopropanol and azobisisobutyronitrile was 1:2.5:0.12; the mass ratio of the powdered solid and KPF6 was 4:3, and the drying conditions were: dried in a vacuum drying oven at 90°C to constant weight; wherein the preparation method of the KPF6 salt solution was: adding KPF6 to deionized water at 65°C and stirring until dissolved; wherein the amount of KPF6 was 0.3g / mL;
[0081] S300, using aluminum isopropoxide and isopropanol to prepare an alumina sol, using 3-aminopropyltriethoxysilane to prepare a silica sol, and mixing the alumina sol and the silica sol to obtain a Si / Al composite sol; specifically:
[0082] S310, preparation of alumina sol: add deionized water to a reactor, raise the temperature to 85°C, add aluminum isopropoxide solution in batches after constant temperature, reflux and stir for 2 hours after all addition is completed to form a white precipitate, then raise the temperature to 95°C, evaporate under stirring until isopropanol is completely volatilized, add hydrochloric acid to redisperse the precipitate, and age for 4 hours to obtain alumina sol; wherein the concentration of hydrochloric acid is 2moL / L, and the mass ratio of aluminum isopropoxide solution, deionized water and hydrochloric acid is 1:1.8:0.25; the preparation method of aluminum isopropoxide solution is: mix aluminum isopropoxide and isopropanol in a mass ratio of 1:2;
[0083] S320, preparation of silica sol: adding 3-aminopropyltriethoxysilane and deionized water into a reactor, stirring at room temperature until a clear transparent solution is obtained to obtain silica sol; wherein the mass ratio of 3-aminopropyltriethoxysilane to deionized water is 7:32;
[0084] S330, mixing the aluminum oxide sol and the silicon oxide sol in a mass ratio of 2:1 to obtain a Si / Al composite sol.
[0085] S400, mixing the obtained white solid with Si / Al composite sol to obtain an antistatic agent; wherein the mass ratio of the white solid to the Si / Al composite sol is 4:15.
[0086] Related tests
[0087] The antistatic agents prepared in Examples 1-3 and Comparative Examples 1-3 were finished, and the finishing method was: the antistatic agent dosage was 25 g / L, and the bath ratio was 1:30; the process flow was: soaking (30 min, residual liquid volume 80%), pre-baking (100°C, 10 min), baking (160°C, 100s), humidity 45%, temperature 20°C environment for 24 h, water washing, and testing.
[0088] Antistatic performance test: refer to GB / T 12703.1-2010 "Evaluation of electrostatic performance of textiles - static voltage half-life" for testing. Before testing, place the fabric at a temperature of 23±2C and an ambient humidity of 40±2% for 24 hours. Surface resistance value: refer to the standard, use PRS-801 surface resistance tester to test the fabric 5 times and take the average value.
[0089] Washing resistance test: refer to the washing process of 4G in GB / T 8629-2017 "Household Washing and Drying Procedure for Textile Testing". The specific method is 2g / L of washing powder, washing at 40℃ for 3 min, bath ratio 1:30, rinsing at room temperature for 3 times, each time for 2 min.
[0090] The test results are shown in Table 1.
[0091] Table 1 Related performance test results
[0092]
[0093] From the test results in Table 1, it can be seen that the antistatic effect of the finished polyester fabric is greatly improved compared with the original polyester fabric. The antistatic effect of the fabric treated with the antistatic agent prepared in Examples 1-3 is better than that of Comparative Examples 1-3; in particular, the antistatic performance of the fabric treated with the antistatic agent prepared in Example 1 is the best; the resistance of the fabric treated with the antistatic agent prepared in Example 1 is 2.4×10 9 Ω, half-life is 0.3s, after washing 10 times, the resistance of the cloth sample is 3.4×10 10 The half-life is 1.8, indicating that the antistatic agent prepared by the present invention has good antistatic performance and washing resistance effect.
[0094] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0095] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an antistatic agent for FDY oiling agent for crude oil, characterized in that: The steps include: S100, mixing triethanolamine and dibasic acid, adding a catalyst, and heating to react to obtain an esterification product; S200, under an inert atmosphere, mixing 4-vinylbenzyl chloride, an esterification product and an antioxidant, and after the temperature reaction is completed, washing, filtering and drying to obtain a powdery solid; S300, under an inert atmosphere, mixing a powdered solid and isopropanol, heating the mixture for 1-2 hours, adding a polymerization initiator, and continuing the reaction for 22-28 hours, raising the temperature, recovering the isopropanol, adding a KPF6 salt solution, stirring at room temperature for 50-60 hours, washing, filtering, and drying to obtain a white solid; S400, preparing an alumina sol using aluminum isopropoxide and isopropanol, preparing a silica sol using 3-aminopropyltriethoxysilane, and mixing the alumina sol and the silica sol to obtain a Si / Al composite sol; S500, mixing the obtained white solid with Si / Al composite sol to obtain the antistatic agent; Step S200 is specifically as follows: in an inert atmosphere, 4-vinylbenzyl chloride, an esterification product and an antioxidant are mixed, the temperature is raised to 75-85° C., and after stirring for 5-10 minutes, flocculent solids appear. After the reaction is continued for 25-30 hours, the plate is tapped several times to monitor the reaction progress. When the raw material is <30% and the change rate is <1% after continuous sampling for 1 hour, the reaction is terminated. When the system is cooled to 40° C., washing, suction filtering and drying are performed to obtain a powdered solid. Step S300 specifically includes: under an inert atmosphere, mixing a powdered solid and isopropanol, raising the temperature to 75-90°C to react for 1-2 hours, adding a polymerization initiator to continue the reaction for 22-28 hours, and then raising the temperature to 95-105°C, condensing and recovering the isopropanol, and when no isopropanol drips out, adding KPF6 salt solution thereto, stirring at room temperature for 50-60 hours, washing, filtering, and drying to obtain a white solid.
2. The method for preparing an antistatic agent according to claim 1, characterized in that: In step S100, the structural formula of the dibasic acid is COOH-(CH2) n -COOH, wherein n is a positive integer not less than 4 and not more than 10.
3. The method for preparing an antistatic agent according to claim 1, characterized in that: Step S100 specifically includes: after mixing triethanolamine and dibasic acid, raising the temperature to 90-105° C., stirring until all solids are dissolved, then adding a catalyst, raising the temperature to 120-135° C., stirring for 4-6 hours, and obtaining an esterification product.
4. The method for preparing an antistatic agent according to claim 3, characterized in that: The catalyst is p-toluenesulfonic acid.
5. The method for preparing an antistatic agent according to claim 1, characterized in that: The antioxidant is 2,6-di-tert-butyl-4-methylphenol.
6. The method for preparing an antistatic agent according to claim 1, characterized in that: The polymerization initiator is azobisisobutyronitrile.
7. The method for preparing an antistatic agent according to claim 1, characterized in that: Step S400 specifically includes: S410, preparation of alumina sol: adding deionized water to a reactor, raising the temperature to 85° C., adding aluminum isopropoxide solution in portions after maintaining the temperature, and refluxing and stirring for 2-3 hours after all the addition is completed to form a white precipitate, then raising the temperature to 95° C., evaporating under stirring until the isopropanol is completely volatilized, adding hydrochloric acid to redisperse the precipitate, and obtaining alumina sol after aging; S420, preparation of silica sol: adding 3-aminopropyltriethoxysilane and deionized water into a reactor, stirring at room temperature until a clear and transparent solution is obtained to obtain silica sol; S430, uniformly mixing the aluminum oxide sol and the silicon oxide sol to obtain a Si / Al composite sol.
8. An antistatic agent for crude oil FDY oil, characterized in that: The antistatic agent is obtained by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
A method for preparing an antistatic agent for spinning oils
CN108547149B
A preparation process of a chemical fiber oil high-efficiency antistatic agent
CN117845379B
Method for preparing initiator for polyamine amphipathic block polyelectrolyte
CN102516428A
Preparation method of polyamine-type amphipathic block polyelectrolyte
CN102516480A